Infidelity and its impact in the perspective of women - Zoiya Naz; Naila Usman (International Journal on Women Empowerment, 2019)
Background: One of the biggest reasons of marital disintegration and domestic violence is infidelity in a marriage. With passing time, Infidelity has become common practice. Men and women see infidelity differently and the cultural differences also categorize infidelity based on the gender of the betrayer especially in the Muslim world. This study was sought to explore the perspective of women regarding infidelity and its impact. Methodology: This observational study was carried out over 100 married women between 21 to 50 years of age. Information was collected through a structured questionnaire based on items related to perspectives, impacts of infidelity and jealousy related patterns among women. The data was gathered by the interviewer after obtaining permission from each respondent. Collected data was then analyzed using SPSS Version 22.0. Results: The results showed that, a significant number of women thought that emotional infidelity (55%) is more harmful as compared to sexual infidelity (40%). The major reason for infidelity according to most women (38%) was the lack of marital satisfaction while 25% suggested loneliness as the reason for infidelity. Moreover, 63% of women suggested that cheating of the partner affects both physical and mental health, while 28% suggested that infidelity act can cause psychological problems. Sexting (60%) & following someone on a social networking site (56%) were thought as the major behaviors of infidelity. 94% women were completely distressed due to sexual relationship of the spouse. Conclusion: The present study showed women’s perceptions regarding infidelity and their experiences, that are significantly important for couple’s therapy and consultations. Thus, for women, infidelity is a reason of divorce, domestic violence and other problems, which harm a woman both physiologically and psychologically.